Differential activation of human neutrophils by SARS-CoV-2 variants of concern - Lebourgeois, Samuel; David, Ambroise; Chenane, Houssem Redha; Granger, Vanessa; Menidjel, Reyene; Fidouh, Nadhira; Noël, Benoît; Delelis, Olivier; Richetta, Clémence; Charpentier, Charlotte; Chollet-Martin, Sylvie; Descamps, Diane; et al. (Frontiers in Immunology, 2022)
The emerging SARS-CoV-2 virus has affected the entire world with over 600 million confirmed cases and 6.5 million deaths as of September 2022. Since the beginning of the pandemic, several variants of SARS-CoV-2 have emerged, with different infectivity and virulence. Several studies suggest an important role of neutrophils in SARS-Cov-2 infection severity, but data about direct activation of neutrophils by the virus is scarce. Here, we studied the in vitro activation of human neutrophils by SARS-CoV-2 variants of concern (VOCs). In our work, we show that upon stimulation with SARS-Cov-2 infectious particles, human healthy resting neutrophils upregulate activation markers, degranulate IL-8, produce Reactive Oxygen Species and release Neutrophil Extracellular Traps. Neutrophil activation was dependent on TLR7/8 and IRF3/STING. We then compared the activation potential of neutrophils by SARS-CoV-2 variants and showed a significantly increased activation by the Delta variant and a decreased activation by the Omicron variant as compared to the initial strain. In this study, we demonstrate that the SARS-Cov-2 virus can directly activate neutrophils in COVID-19 and that the different VOCs had differences in neutrophil activation intensity that mirror the differences of clinical severity. These data highlight the need to address neutrophil-virus interactions as a potential target for therapeutic intervention in SARS-CoV-2 infection.